2011
DOI: 10.1063/1.3569629
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensitivity to direct current magnetic field changes in Metglas/Pb(Mg1/3Nb2/3)O3–PbTiO3 laminates

Abstract: Articles you may be interested inWe have developed Metglas/Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 magnetoelectric (ME) laminates that have notably larger ME coefficients, with maximum values of up to 45 V/cm Oe. Based on this giant ME effect, the dc magnetic field sensitivity for Metglas/PMN-PT laminate sensors was improved by a factor of > 3, relative to that for Metglas/Pb(Zr,Ti)O 3 (PZT)-based ones of the same geometry. Our new ME sensor can detect dc magnetic field changes as small as (i) 5 nT at 1 kHz and (ii) 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 14 publications
1
26
1
Order By: Relevance
“…DC magnetic field variations as small as H dc ¼ 15 nT could be detected under a 0.1 Oe, 1 kHz drive for the sensor with Metglas foils of 80 mm in length, similar to recent reports. 10 However, the DC magnetic field changes as small as 6 nT were detectable by using ME sensor with longer Metglas foils (100 mm); note that similar drive conditions were used. This represents a 250% increase in the DC field sensitivity.…”
Section: -mentioning
confidence: 99%
“…DC magnetic field variations as small as H dc ¼ 15 nT could be detected under a 0.1 Oe, 1 kHz drive for the sensor with Metglas foils of 80 mm in length, similar to recent reports. 10 However, the DC magnetic field changes as small as 6 nT were detectable by using ME sensor with longer Metglas foils (100 mm); note that similar drive conditions were used. This represents a 250% increase in the DC field sensitivity.…”
Section: -mentioning
confidence: 99%
“…6 Strain-mediated ME effects in bulk ferromagnetic/ferroelectric laminate materials were intensively developed by Ryu et al in the early 2001, 7 which represented a great step forward in the revival of ME materials with the highest value of 1100 V cm À1 Oe À1 in resonance conditions reported to date. 8 In the last decade, converse magnetoelectric effects have received an ever-increasing attention and provoked versatile proposals for development of multifunctional CME devices, 9,10 including tunable inductors, 11,12 RF/microwave opintronics, 13 MERAMs, 14 and coil-less flux switch. 15 For example, Chen et al demonstrated an electrically controlled magnetization switching in a FeCoV/PMN-PT [Pb(Mg 1/3 Nb 2/3 )O 3 -PbTiO 3 ] strain-mediated multiferroic heterostructure, exhibiting a maximum CME coupling of 2.2 Â 10 À7 sÁm À1 with the assistance of a magnetic bias field $160 Oe.…”
mentioning
confidence: 99%
“…This figure shows that the cross-modulation scheme has the ability of transferring low frequency magnetic signal (1 Hz) to higher frequencies (29.499 kHz and 29.501 kHz), where the noise floor is much lower than that at low frequency. 26 Please note that the effectiveness of this frequency transfer is proportional to the nonlinear ME coefficient a Nonlin ME . This is the reason why in this paper we tried to determine the conditions under which the nonlinear ME coefficient a Nonlin ME was maximized.…”
Section: Furthermore Inspection Of Figs 4(c) and 4(d) Will Reveal Tmentioning
confidence: 99%